Peran Budaya Organisasi terhadap Kesehatan Mental Mahasiswa - Lingga, Angga Fernanda Putra; Sri Nurhayati Selian1 (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2025)
This study explores the role of campus organizational culture in shaping the mental health of university students actively involved in student organizations. The study aims to obtain an in-depth understanding of how organizational values, leadership practices, communication patterns, and social interactions influence students’ psychological well-being. A qualitative descriptive phenomenological approach was employed. Data were collected through in-depth semi-structured interviews, observations, and documentation involving three undergraduate students actively engaged in campus organizations in Banda Aceh. The data were analyzed using thematic analysis to identify recurring patterns and meanings in participants’ experiences. The findings indicate that organizational cultures characterized by solidarity, open communication, democratic leadership, and strong social support contribute positively to students’ mental health by fostering emotional safety, motivation, and resilience. Conversely, hierarchical, overly competitive, and unsupportive organizational cultures were found to increase psychological pressure, stress, and emotional exhaustion. This study contributes to the understanding of campus organizations as psychosocial environments and highlights the importance of developing healthy, inclusive, and empathetic organizational cultures to promote students’ mental well-being in higher education settings.